IMPLEMENTASI SISTEM KENDALI PID PADA KECEPATAN MOTOR PENGADUK MESIN PRODUKSI KITOSAN - Rizki Akbar Prayogo P , Akbar; Ari Murtono; Imam Saukani (CV SWA Anugerah, 2025)
Indonesia is a country that has a larger water area than land, so its fishery products are abundant. One of the more potential products is crab. Some studies mention that the shell of the crab contains chitin which can be converted into chitosan through a deacetylation reaction. This chitosan is useful as a food preservative, supplement, anti-microbial, water purifier, anti-oxidant and fat absorber. Currently, the previous work is less effective if done in a conventional way for chitosan production which requires constant temperature stability and stirring speed. Because the viscosity quality standard in the stirring production process affects the speed that can produce an even mixing process until the resulting chitosan color becomes white or yellowish powder. Where the color of the white or yellowish powder itself is a quality parameter of chitosan. In this problem, the author tries to implement a PID control system in the chitosan stirring process. This machine uses a DC gearbox motor as the main drive and utilizes Arduino PWM to adjust the motor speed, so that the machine can be adjusted according to the user's wishes. The power window motor is used to drive the stirrer, which can be adjusted to the desired chitosan viscosity. In use, the user can enter input on the keypad. In the manufacture of this machine, the thing to be achieved can adjust the motor speed of 100 Rpm when stirring the chitosan so that the viscosity and color of the chitosan reach the desired quality standards, namely with a viscosity of 200-700cps and white or yellowish powder color parameters.